Visual outcome and efficacy of conjunctival autograft, harvested from the body of pterygium in pterygium excision - Bhandari V (Dove Medical Press, 2015)
Vipul Bhandari, Chandan Latha Rao, Sri Ganesh, Sheetal Brar Department of Cornea, Nethradhama Superspeciality Eye Hospital, Bangalore, India Purpose: To evaluate the efficacy of conjunctival autograft after the pterygium excision with fibrin adhesive using conjunctiva over the pterygium.Patients and methods: This prospective study included 25 eyes of 25 patients with a mean age of 40±10 years, who underwent the pterygium excision with conjunctival autograft derived from the body of the pterygium and attached using fibrin glue. The mean follow-up period was 6 months. On all postoperative visits, changes in uncorrected visual acuity, corrected distance visual acuity, astigmatism, complications, and the evidence of recurrence were recorded.Results: At the end of mean follow-up, uncorrected visual acuity and corrected distance visual acuity improved by one or two lines in all eyes treated. Mean astigmatism reduced significantly from a preoperative value from 2.308D to 1.248D postoperatively (P<0.026). Minor postoperative complications such as congestion, chemosis, and subconjunctival hemorrhage were seen, which resolved with time. No major sight-threatening or graft-related complications were detected. There was no evidence of recurrence during a follow-up period of 6 months.Conclusion: Self-conjunctival autograft following the pterygium excision appears to be a feasible, safe, and effective alternative method for management of pterygium. It also preserves the superior conjunctiva for future surgeries. However, longer follow-up is required to study the long-term outcomes, especially the incidence of recurrence. Keywords: Pterygium, self-conjunctival graft, body, autograft